2020
DOI: 10.1002/mp.14350
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative computed tomography‐guided disease‐free survival prediction in gastric cancer: a multicenter radiomics study

Abstract: Preoperative and noninvasive prognosis evaluation remains challenging for gastric cancer. Novel preoperative prognostic biomarkers should be investigated. This study aimed to develop multidetector-row computed tomography (MDCT)-guided prognostic models to direct follow-up strategy and improve prognosis. Methods: A retrospective dataset of 353 gastric cancer patients were enrolled from two centers and allocated to three cohorts: training cohort (n = 166), internal validation cohort (n = 83), and external valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Radiomics utilizes automated quantitative characterization algorithms to transform a large number of excavatable spatial ROI-based image data into representative and effective radiomic features [ 6 ]. Recent advancements in radiomics have provided new ideas for individualized management of GC, including lymphatic metastasis prediction [ 7 , 8 ], distant metastasis prediction [ 9 ], therapeutic response evaluation [ 10 ], and prognostic evaluation [ 11 , 12 ]. These studies highlighted the value of radiomics, suggesting that radiomics could be a potential tool for the Lauren classification in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics utilizes automated quantitative characterization algorithms to transform a large number of excavatable spatial ROI-based image data into representative and effective radiomic features [ 6 ]. Recent advancements in radiomics have provided new ideas for individualized management of GC, including lymphatic metastasis prediction [ 7 , 8 ], distant metastasis prediction [ 9 ], therapeutic response evaluation [ 10 ], and prognostic evaluation [ 11 , 12 ]. These studies highlighted the value of radiomics, suggesting that radiomics could be a potential tool for the Lauren classification in GC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MDCTbased texture features such as the apparent diffusion coefficient seem to be promising biomarkers for the evaluation of the aggressiveness (T and N stage), treatment response and prognosis of gastric cancer [30]. Furthermore, MDCT imaging biomarkers hold promise as prognostic factors, with potential for guiding treatment and follow-up strategy [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis is the research highlight of AI-based studies and numerous researchers have explored the potential of hand-crafted radiomics and DL features for prognosis prediction ( 10 , 18 , 20 , 23 , 25 , 30 , 33 , 34 , 43 46 , 53 , 60 ). Nine studies directly correlated hand-crafted radiomics and DL features with prognosis ( 10 , 18 , 20 , 23 , 30 , 44 , 46 , 53 , 60 ), and five constructed AI-based models to predict certain clinicopathological features, which were shown to be related to prognosis ( 25 , 33 , 34 , 43 , 45 ). Only one study extracted hand-crafted radiomics features from PET images ( 23 ), whereas all others used CT images ( 10 , 13 , 18 22 , 25 , 30 , 33 , 34 , 43 46 , 53 , 60 ).…”
Section: Clinical Applications Of Hand-crafted Radiomics and Deep Learning In Gastric Cancermentioning
confidence: 99%
“…Nine studies directly correlated hand-crafted radiomics and DL features with prognosis ( 10 , 18 , 20 , 23 , 30 , 44 , 46 , 53 , 60 ), and five constructed AI-based models to predict certain clinicopathological features, which were shown to be related to prognosis ( 25 , 33 , 34 , 43 , 45 ). Only one study extracted hand-crafted radiomics features from PET images ( 23 ), whereas all others used CT images ( 10 , 13 , 18 22 , 25 , 30 , 33 , 34 , 43 46 , 53 , 60 ). Earlier studies reported OS-related hand-crafted radiomics features ( 10 , 18 ), with later studies building hand-crafted radiomics and DL models that integrated hand-crafted radiomics features with and without clinicopathological features; these achieved good performance in OS, disease-free survival (DFS), and early recurrence prediction ( 20 , 23 , 30 , 33 , 44 ).…”
Section: Clinical Applications Of Hand-crafted Radiomics and Deep Learning In Gastric Cancermentioning
confidence: 99%